Cytotoxic effect of nanocrystalline MgFe2O4 particles for cancer cure - Kanagesan, Samikannu; Hashim, Mansor; Subramani, Tamilselvan; Mohammed Alitheen, Noorjahan Banu; Ismail, Ismayadi; Bahmanrokh, Ghazaleh (Hindawi Publishing Corporation, 2013)
Nanocrystalline magnesium ferrites (MgFe2O4) were produced with an average grain size of about 20 nm. Their structural, morphological, and magnetic characterizations were studied. The cytotoxic effects of MgFe2O4 nanoparticles in various concentrations (25, 50, 100, 200, 400, and 800 μg/mL) against MCF-7 human breast cancer cells were analyzed. MTT assay findings suggest the increased accumulation of apoptotic bodies with the increasing concentration of MgFe2O4 nanoparticles in a dose-dependent manner. Flow cytometry analysis shows that MgFe2O4 nanoparticles in 800 μg/mL concentration are more cytotoxic compared to vehicle-treated MCF-7 cells and suggests their potential utility as a drug carrier in the treatment of cancer.